LAP-like non-canonical autophagy and evolution of endocytic vacuoles in pancreatic acinar cells - De Faveri, Francesca (Autophagy, 2019)
Activation of trypsinogen (formation of trypsin) inside the pancreas is an early pathological event in the development of acute pancreatitis. In our previous studies we identified the activation of trypsinogen within endocytic vacuoles (EVs), cellular organelles that appear in pancreatic acinar cells treated with the inducers of acute pancreatitis. EVs are formed as a result of aberrant compound exocytosis and subsequent internalization of post-exocytic structures. These organelles can be up to 12 μm in diameter and can be actinated (i.e. coated with F-actin). Notably, EVs can undergo intracellular rupture and fusion with the plasma membrane, providing trypsin with access to cytoplasmic and extracellular targets. Unraveling the mechanisms involved in cellular processing of EVs is an interesting cell biological challenge with potential benefits for understanding acute pancreatitis. In this study we have investigated autophagy of EVs and discovered that it involves a non-canonical LC3-conjugation mechanism, reminiscent in its properties to LC3-associated phagocytosis (LAP); in both processes LC3 was recruited to single, outer organellar membranes. Trypsinogen activation peptide was observed in approximately 55% of LC3-coated EVs indicating the relevance of the described process to the early cellular events of acute pancreatitis. We also investigated relationships between actination and non-canonical autophagy of EVs and concluded that these processes represent sequential steps in the evolution of EVs. Our study expands the known roles of LAP and indicates that, in addition to its well-established functions in phagocytosis and macropinocytosis, LAP is also involved in the processing of post-exocytic organelles in exocrine secretory cells. ABBREVIATIONS: AP: acute pancreatitis; CCK: cholecystokinin; CLEM: correlative light and electron microscopy; DPI: diphenyleneiodonium; EV: endocytic vacuole; LAP: LC3-associate phagocytosis; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; PACs: pancreatic acinar cells; PFA: paraformaldehyde; PtdIns3K: phosphatidylinositol 3-kinase; PtdIns3P: phosphatidylinositol 3-phosphate; Res: resveratrol; TAP: trypsinogen activation peptide; TEM: transmission electron microscopy; TLC-S: taurolithocholic acid 3-sulfate; TRD: Dextran Texas Red 3000 MW Neutral; ZGs: zymogen granules.